Psychometric Properties of the Persian Version of the Care Transitions Measure (CTM-15) in Iranian Older People - Seyed Ebrahim Seyed Alavi; Farahnaz Mohammadi-Shahboulaghi; Mohammad Ali Hosseini; mohsen vahedi; Maryam Khoshbakht-Pishkhani; Nasim Sadeghi Mahalli (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives The care transitions measure (CTM-15) is a reliable and valid tool to evaluate the transition of care. This study aims to assess the psychometric properties of the Persian version of CTM-15 in Iranian older people. Methods & Materials This is a psychometrics study. The questionnaire was first translated into Persian based on the international quality of life assessment protocol. Then, it was completed by 200 older people who were selected using a convenience sampling method based on the inclusion criteria. After completion, face validity, content validity, construct validity (using confirmatory factor analysis and exploratory factor analysis) and convergent validity were investigated. The reliability of the questionnaire was evaluated in terms of internal consistency (using Cronbach's α) and test-retest reliability. Statistical analyses were done in SPSS software, version 26 and AMOS software, version 24. Results The content validity index (CVI) for the whole questionnaire was obtained as S-CVI=0.966. Following CFA, the 4-factor solution was not confirmed and did not show a good fit (P<0.001, RMSEA=0.093, GFI=0.851, NFI=0.644, CFI=0.731). After performing EFA, three factors were found and named as "patient and caregiver preferences", "self-management and follow-up" and "medication management". Convergence validity of the Persian CTM-15 with GSE-10 was assessed using Pearson's correlation test which obtained as r=0.468. The internal consistency using Cronbach's α coefficient was 0.76 and intraclass correlation coefficient was 0.85. Conclusion The Persian version of CTM-15 did not support the 4-factor model of the original version. The Persian version with 3 subscales, due to having acceptable validity and reliability, can be used as an efficient tool to evaluate the transition of care for the elderly in Iran. The benefits of measuring the transition of care and its impact on the promotion of discharge programs and continuity of care in various settings justify the need to pay attention to this tool.